Meningkatkan Kesadaran Masyarakat Akan Kebersihan dan Keamanan Jamu Gendong Untuk Meningkatkan Daya Saing: Increasing Public Awareness Of The Cleanliness And Safety Of Jamu Gendong To Increase Competitiveness - Muchayatin; Joko Riyanto; Dirgo Wahyono; Melanita Kristiani; Nur Rohmad (Universitas 17 Agustus 1945 Semarang, 2023)
In recent years, there has been a phenomenon of people's tendency to return to nature (Back To Natur), and drink herbal medicine as one of the lifestyles. So as to encourage the herbal medicine industry to compete to innovate products and packaging, not to forget the jamu carrying. The purpose of this community service is to change the minset of the community that has been leaning towards treatment with chemical drugs, turning to herbal products, especially carrying herbs whose ingredients are made from plants around us that are beneficial for health and fitness. The method used lectures, dialogues and discussions. The results obtained in this service discussion of jamu gendong enthusiasts still have a positive perception of the benefits and properties of jamu gendong, the desire to be registered with the POM Agency, the need for assistance in the production, packaging and marketing processes